Nano and microstructural design of advanced materials : a commemorative volume on Professor G. Thomas' seventieth birthday - Thomas, Gareth, 1932-2014.; Meyers, Marc A.; Ritchie, R. O. (Robert O.); Sarikaya, Mehmet; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2003)
The importance of the nanoscale effects has been recognized in materials research for over fifty years, but it is only recently that advanced characterization and fabrication methods are enabling scientists to build structures atom-by-atom or molecule-by molecule. The understanding and control of the nanostructure has been, to a large extent, made possible by new atomistic analysis and characterization methods pioneered by transmission electron microscopy. Nano and Microstructural Design of Advanced Materials focuses on the effective use of such advanced analysis and characterization techniques in the design of materials. * Teaches effective use of advanced analysis and characterization methods at an atomistic level. * Contains many supporting examples of materials in which such design concepts have been successfully applied.
Front Cover; Nano and Microstructural Design of Advanced Materials; Copyright Page; Preface; Curriculum Vitae of Professor Thomas; Table of Contents; Part 1: Characterization; Chapter 1. Characterization: The Key to Materials; Chapter 2. Nanochemical and Nanostructural Studies of the Brittle Failure of Alloys; Chapter 3. Transmission Electron Microscopy Study of the Early-Stage Precipitates in Al-Mg-Si Alloys; Chapter 4. Laser Surface Alloying of Carbon Steels with Tantalum, Silicon and Chromium; Chapter 5. In-Situ TEM Observation of Alloying Process in Isolated Nanometer-Sized Particles.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Elsevier
Keywords: Nanostructured materials; Materials -- Microscopy; TECHNOLOGY & ENGINEERING -- Material Science; Materials -- Microscopy; Nanostructured materials; Materiais; Nanotecnologia; Electronic books